(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In the modern healthcare system, a specialist engaged in professional activity is required not only to have deep theoretical knowledge but also a high level of practical skills, communication culture, clinical thinking, and the ability to make independent decisions — that is, a set of complex professional competences. Especially, the work of medical personnel, which is directly related to the life and health of patients, requires the continuous development of these competences.